2017
DOI: 10.1111/asj.12798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of iodixanol to semen extender on quality and fertilization ability of frozen–thawed Thai native bull sperm

Abstract: This study investigates the effects of iodixanol supplementation in varied concentrations to Tris egg yolk (TEY) extender on the quality and fertilization ability of frozen-thawed sperm of Thai native bulls. Each ejaculate was divided into four different groups, as follows: sperm were treated with TEY extender (control group) and TEY extender supplemented with three different concentrations of iodixanol (1.25%, 2.50% and 5.00%). Semen straws were frozen in liquid nitrogen vapor. After thawing, sperm motility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Regarding the G3, although it did not differ from G6 for almost all semen quality parameters, this iodixanol concentration was not effective for providing greater longevity to the sperm. Similarly, other authors reported that 5% (final concentration 3%, v/v) is potentially toxic to bull and buffalo sperm (Chuawongboon et al, 2017; Saragusty et al, 2009; Swami et al, 2017a) although this concentration was optimal for freezing ram semen (Cirit et al, 2013). According to Chuawongboon et al (2017), the toxicity of higher doses of iodixanol is related to an increase in the osmolarity of extracellular solution, which was not observed in this study with G6.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Regarding the G3, although it did not differ from G6 for almost all semen quality parameters, this iodixanol concentration was not effective for providing greater longevity to the sperm. Similarly, other authors reported that 5% (final concentration 3%, v/v) is potentially toxic to bull and buffalo sperm (Chuawongboon et al, 2017; Saragusty et al, 2009; Swami et al, 2017a) although this concentration was optimal for freezing ram semen (Cirit et al, 2013). According to Chuawongboon et al (2017), the toxicity of higher doses of iodixanol is related to an increase in the osmolarity of extracellular solution, which was not observed in this study with G6.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, other authors reported that 5% (final concentration 3%, v/v) is potentially toxic to bull and buffalo sperm (Chuawongboon et al, 2017; Saragusty et al, 2009; Swami et al, 2017a) although this concentration was optimal for freezing ram semen (Cirit et al, 2013). According to Chuawongboon et al (2017), the toxicity of higher doses of iodixanol is related to an increase in the osmolarity of extracellular solution, which was not observed in this study with G6. The osmotic strength of commercial iodixanol solution is 170 mOsm/kg, thus any addition of this substance would maintain or reduce the extracellular osmolarity and, consequently, the damage from the high‐osmolarity effect (Saragusty et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…During the sperm treatment, trehalose binds to the sperm cell membrane, which reduces the damage of the sperm caused by dehydration and the damage to the acrosomal and plasma membranes, thus stabilizing sperm cell membrane structure (Nayernia et al, 2002;Zhu et al, 2017). The proteolytic enzymes (acrosome enzymes) existing in sperm acrosomes are critically involved in the fertilization process (He et al, 2016;Chuawongboon et al, 2017). The detection of the acrosome integrity can indirectly reflect the sperm function, which is of great significance in the evaluation of abnormal sperm function and artificial insemination effectiveness.…”
Section: Discussionmentioning
confidence: 99%